1998
DOI: 10.1016/s0014-5793(98)00632-2
|View full text |Cite
|
Sign up to set email alerts
|

An essential role of NFκB in tyrosine kinase signaling of p38 MAP kinase regulation of myocardial adaptation to ischemia

Abstract: We have recently demonstrated that myocardial adaptation to ischemia triggers a tyrosine kinase regulated signaling pathway leading to the translocation and activation of p38 MAP kinase and MAPKAP kinase 2. Since oxidative stress is developed during ischemic adaptation and since free radicals have recently been shown to function as an intracellular signaling agent leading to the activation of nuclear transcription factor, NFU UB, we examined whether NFU UB was involved in the ischemic adaptation process. Isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(140 citation statements)
references
References 35 publications
6
133
0
1
Order By: Relevance
“…The functional importance of p38 MAPK in MMP-2 expression in melanoma cells was also suggested by a recent report showing that inhibition of p38 MAPK by the specific inhibitor SB203580 down-regulated MMP-2 expression resulting in reduced invasive potential of malignant melanoma cells (45). Moreover, in different cell types, the p38 MAPK-dependent pathway interferes with the transactivation properties of NF-nB (46)(47)(48). Although the mechanisms by which p38 MAPK activates NF-nB are controversial, with evidence supporting regulation of NF-nBdependent gene transcription via modulation of activation of the transcription factor IID and/or post-translational modifications, including phosphorylation and acetylation, of the RelA/p65 subunit, our data strongly suggest that mda-9/syntenin stimulates MMP-2 expression by activating MT1-MMP through the p38 MAPK and NF-nB pathways leading to melanoma cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The functional importance of p38 MAPK in MMP-2 expression in melanoma cells was also suggested by a recent report showing that inhibition of p38 MAPK by the specific inhibitor SB203580 down-regulated MMP-2 expression resulting in reduced invasive potential of malignant melanoma cells (45). Moreover, in different cell types, the p38 MAPK-dependent pathway interferes with the transactivation properties of NF-nB (46)(47)(48). Although the mechanisms by which p38 MAPK activates NF-nB are controversial, with evidence supporting regulation of NF-nBdependent gene transcription via modulation of activation of the transcription factor IID and/or post-translational modifications, including phosphorylation and acetylation, of the RelA/p65 subunit, our data strongly suggest that mda-9/syntenin stimulates MMP-2 expression by activating MT1-MMP through the p38 MAPK and NF-nB pathways leading to melanoma cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Because cell shrinkage caused by hypertonicity is a regulatory signal for the p38 MAPK activation [14,34], the cell size difference between fibroblasts cultured in fl-coll and att-coll might be one of the signals that activate the p38 MAPK. In fact, a number of physiological or disease processes that involve morphological alterations, such as ischaemic and hypertensive myocardial disease, also require p38 MAPK activation [12,35]. The specific activation of fibroblast p38α by fl-coll is consistent with observations that p38 MAPK mediates mitotic arrest [36] and apoptosis [37], two cellular functions associated with fibroblasts cultured in contracting collagen matrices, but not att-coll [2,38].…”
Section: Discussionsupporting
confidence: 76%
“…The inhibition of p38α by SB203580 at concentrations from 0.1 µM to 10 µM blocked transactivation activity of NF-κB in a one-way concentration-dependent manner ( Figure 6C), suggesting that NF-κB activation by fl-coll requires p38α activity. Depending on the extracellular signals, p38-mediated NF-κB activation is manifested by nuclear translocation [12], phosphorylation of p65 itself [13] or association of NF-κB with basal transcription factors such as TFIIB and TATA-binding protein [11]. Because we have shown that fl-coll induces NF-κB nuclear translocation [1], the effects of p38α on DNA binding of NF-κB and the nuclear presence of p50 and p65, two subunits previously identified present in the NF-κB DNA-binding complex in fl-coll-induced fibroblasts [1], were examined.…”
Section: Nf-κb Is a Downstream Target Of P38α In Fibroblasts Surroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible interaction between p38 MAPK and NFkB was first suggested by Maulik et al (1998). They presented evidence that the p38 inhibitor SB203580 prevents NFkB nuclear translocation during ischemic adaptation.…”
Section: Discussionmentioning
confidence: 97%